Mobilizing practitioners to support the Emergency Recovery Plan for freshwater biodiversity. Issue 8 (8th June 2021) - Twardek, William M.; Nyboer, Elizabeth A.; Tickner, David; O'Connor, Constance M.; Lapointe, Nicolas W. R.; Taylor, Mark K.; Gregory‐Eaves, Irene; Smol, John P.; Reid, Andrea J.; Creed, Irena F.; Nguyen, Vivian M.; Winegardner, Amanda K.; et al.
Abstract: Freshwater biodiversity loss is one of the greatest environmental threats in our changing world. Although declines have been reported extensively in the literature, much less attention has been devoted to solving the freshwater biodiversity crisis relative to other ecosystems. The recently proposed Emergency Recovery Plan for Freshwater Biodiversity (Tickner et al., 2020, BioScience, 70 (4), 330–342) outlines an ambitious but necessary set of overarching actions that can help "bend the curve" for freshwater biodiversity declines. This plan is timely given the present opportunity to adjust freshwater biodiversity targets in international biodiversity agreements and to encourage meeting targets of relevant Sustainable Development Goals. Yet, relying solely on a trickle down from such agreements to national and local scales will likely take too long, given the immediate urgency of the situation. Here, we advocate for a broader, concerted effort from all actors to ensure the Emergency Recovery Plan meaningfully influences the actions of practitioners at a local scale. We outline the roles and responsibilities of actors involved with policy, research, professional bodies and societies, advocacy, and industry, as well as practitioners themselves, in achieving this goal. It is our hope that this overview facilitates the real‐world actions needed to execute the Emergency Recovery Plan so that we can indeed "bend the curve" for freshwater biodiversity. Abstract : The recently proposed Emergency Recovery Plan for Freshwater Biodiversity (Tickner et al., 2020, BioScience, 70 (4), 330–342) outlines an ambitious but necessary set of overarching actions that can help "bend the curve" for freshwater biodiversity declines. It takes time for such plans to influence the small‐scale actions taken by practitioners working on the ground, but we do not have time to wait given the immediate urgency of the situation. Here, we advocate for a broader, concerted effort from all actors to ensure the Emergency Recovery Plan meaningfully influences the actions of practitioners at a local scale.